Development, validation, and evaluation of a web- based behaviour intervention (chance2act) to act for weight loss for adults with type 2 diabetes mellitus and body mass index of ≥ 23kg/m - Mohd Saad, Noraini (2024)
Background: In adults with type 2 diabetes (T2D), weight loss has been shown to improve haemoglobin A1C, blood pressure, triglyceride levels, health-related quality of life, and reduce the need for medications. Although the majority of patients with T2D are either overweight or obese, many are not ready to act for weight loss. This study aimed to develop, validate, and evaluate a behavioural change intervention for adults with T2D and obesity who are not ready to act for weight loss. Methodology: The development of the health intervention was guided by the Intervention Mapping (IM) framework, which comprises six steps. Content development was conducted in the initial three steps of the IM framework. Step 1 involved the creation of a Logic Model of the Problem to summarize the findings from the needs assessment. Step 2 focused on developing Matrices of Change Objectives, which outlined the preliminary content for the intervention. This content was refined in Step 3, into the final themes, scopes, and activities of the intervention. In Step 4, the content was validated using both Content Validity Index (I-CVI) and Scale Content Validity Index/Average (S-CVI/Ave) to ensure content relevance, and Face Validity Index (I-FVI) and Scale Face Validity Index/Average (S-FVI/Ave) to confirm the clarity, simplicity and unambiguity of the intervention. Additionally, the usability testing of the intervention website was done to ensure it met the recommended standards of website usability. Phase 2, which encompassed the remaining two steps of the IM framework. The pilot study was conducted as a non-randomized controlled trial in Beserah Health Clinic (Intervention) and Paya Besar Health Clinic (control) in Kuantan, Pahang. The study employed an unblinded, parallel assignment design, with a 1:1 allocation ratio. Results: During Phase 1, the content was successfully developed into the Manual of the Chance2Act Intervention. The validation study showed good content validity (I-CVI and S-CVI/Ave = 1.00) and high face validity (I-FVI and S-FVI/Ave > 0.9) across all criteria. After being transformed into a website, the usability testing yielded a System Usability Score (SUS) of 69.5, exceeding the recommended threshold. Phase 2 results indicated significant within-group improvements in the intervention group, particularly in the progression across stages of change after two months (P-value = 0.02) and selfefficacy for a healthy diet in availability subscale at one and two months, with a P-value of 0.002 and 0.03, respectively. Discussion: The meticulous development of the intervention, guided by the Intervention Mapping (IM) framework, ensured a systematic approach to addressing the health issue. This structured methodology is reflected in the validation results, which demonstrated high content and face validity for the intervention components. However, the SUS score has just met the minimum threshold, which highlighted usability issues and observed challenges with maintaining intervention fidelity. Phase 2 results were inconclusive due to several limitations particularly the time constraint which restricted the ability to assess the intervention's effects fully. Conclusion: This research has successfully achieved its initial objectives. However, its effect to promote behaviour change cannot be demonstrated due to the study’s limitations including the challenges to maintain the intervention protocol fidelity and short study duration. Further studies are recommended to refine the intervention development, enhance the website usability and its implementation strategies to accelerate the readiness to act for weight loss within this population